The Impact of ChatGPT Usage on Academic Performance: The Mediating Role of Self-Regulated Learning - Kok Ban Teoh; Rudresh Pandey; Mengge Zhang; Yiming Zhang; Yonghan Zhang; Ruidong Zhen; Aarushi Jatian; Shivi Srivastava; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2026)
The increasing adoption of generative artificial intelligence tools, particularly ChatGPT, has transformed the way students approach learning and academic tasks in higher education. This study examines the effect of ChatGPT usage on students’ academic performance and analyses the mediating role of self-regulated learning. A quantitative research design was employed, and data were collected from 20 higher education students using a structured questionnaire. ChatGPT usage was treated as the independent variable, self-regulated learning as the mediating variable, and academic performance as the dependent variable. The findings show that ChatGPT usage has a positive effect on academic performance and self-regulated learning. The results also indicate that self-regulated learning positively influences academic performance and mediates the relationship between ChatGPT usage and academic performance. These findings suggest that ChatGPT can support students by improving learning efficiency, providing quick access to information, and assisting with academic tasks